Satisfaction Level of Outpatients at Lengko Ajang Public Center, East Manggarai Regency - Yosefina Jelina; Yoseph Kenjam; Rina Waty Sirait (Lontar : Journal of Community Health, 2022)
Service quality is an element that can affect patient satisfaction while undergoing health services at the public health center. Patient satisfaction in health services is measured by five indicators: tangible, responsiveness, reliability, empathy, and assurance. These five aspects are closely related to humans as service providers and assessed very subjectively from the perspective of the community (patients) and aspect of the assessment. This study aimed to determine outpatients' satisfaction at the Lengko Ajang Puskesmas, East Manggarai Regency. The method used in this research is descriptive-analytic. The sample in this study amounted to 79 outpatients at Lengko Ajang Puskesmas. The sampling technique used purposive sampling. The result showed that outpatients' satisfaction at the Lengko Ajang Puskesmas was in the very satisfied category for tangible, reliability, empathy, and assurance dimensions. Only was the responsiveness dimension in the satisfied category. Overall, the satisfaction level of outpatients at the Lengko Ajang Puskesmas is in the very satisfied category and therefore needs to be maintained by the provider